Clinical predictors of dengue fever co-infected with leptospirosis among patients admitted for dengue fever - a pilot study - Suppiah, Jeyanthi; Chan, Shie Yien; Ng, Min Wern; Khaw, Yam Sim; Ching, Siew Mooi; Mat Nor, Lailatul Akmar; Ahmad Najimudin, Naematul Ain; Chee, Hui Yee (BioMed Central, 2017)
Background: Dengue and leptospirosis infections are currently two major endemics in Malaysia. Owing to the overlapping clinical symptoms between both the diseases, frequent misdiagnosis and confusion of treatment occurs. As a solution, the present work initiated a pilot study to investigate the incidence related to co-infection of leptospirosis among dengue patients. This enables the identification of more parameters to predict the occurrence of co-infection. Method: Two hundred sixty eight serum specimens collected from patients that were diagnosed for dengue fever were confirmed for dengue virus serotyping by real-time polymerase chain reaction. Clinical, laboratory and demographic data were extracted from the hospital database to identify patients with confirmed leptospirosis infection among the dengue patients. Thus, frequency of co-infection was calculated and association of the dataset with dengue-leptospirosis co-infection was statistically determined. Results: The frequency of dengue co-infection with leptospirosis was 4.1%. Male has higher preponderance of developing the co-infection and end result of shock as clinical symptom is more likely present among co-infected cases. It is also noteworthy that, DENV 1 is the common dengue serotype among all cases identified as dengue-leptospirosis co-infection in this study. Conclusion: The increasing incidence of leptospirosis among dengue infected patients has posed the need to precisely identify the presence of co-infection for the betterment of treatment without mistakenly ruling out either one of them. Thus, anticipating the possible clinical symptoms and laboratory results of dengue-leptospirosis co-infection is essential.